The impact of cryopreserved sperm on intrauterine insemination outcomes: is frozen as good as fresh? - Cherouveim, Panagiotis; Vagios, Stylianos; Hammer, Karissa; Fitz, Victoria; Jiang, Victoria S.; Dimitriadis, Irene; Sacha, Caitlin R.; James, Kaitlyn E.; Bormann, Charles L.; Souter, Irene (Frontiers in Reproductive Health, 2023)
Introduction Frozen sperm utilization might negatively impact cycle outcomes in animals, implicating cryopreservation-induced sperm damage. However, in vitro fertilization and intrauterine insemination (IUI) in human studies are inconclusive. Methods This study is a retrospective review of 5,335 IUI [± ovarian stimulation (OS)] cycles from a large academic fertility center. Cycles were stratified based on the utilization of frozen (FROZEN, n = 1,871) instead of fresh ejaculated sperm (FRESH, n = 3,464). Main outcomes included human chorionic gonadotropin (HCG) positivity, clinical pregnancy (CP), and spontaneous abortion (SAB) rates. Secondary outcome was live birth (LB) rate. Odds ratios (OR) for all outcomes were calculated utilizing logistic regression and adjusted (adjOR) for maternal age, day-3 FSH, and OS regimen. Stratified analysis was performed based on OS subtype [gonadotropins; oral medications (OM): clomiphene citrate and letrozole; and unstimulated/natural]. Time to pregnancy and cumulative pregnancy rates were also calculated. Further subanalyses were performed limited to either the first cycle only or to the partner's sperm only, after excluding female factor infertility, and after stratification by female age (<30, 30–35, and >35 years old). Results Overall, HCG positivity and CP were lower in the FROZEN compared to the FRESH group (12.2% vs. 15.6%, p < 0.001; 9.4% vs. 13.0%, p < 0.001, respectively), which persisted only among OM cycles after stratification (9.9% vs. 14.2% HCG positivity, p = 0.030; 8.1% vs. 11.8% CP, p = 0.041). Among all cycles, adjOR (95% CI) for HCG positivity and CP were 0.75 (0.56–1.02) and 0.77 (0.57–1.03), respectively, ref: FRESH. In OM cycles, adjOR (95% CI) for HCG positivity [0.55 (0.30–0.99)] and CP [0.49 (0.25–0.95), ref.: FRESH] favored the FRESH group but showed no differences among gonadotropin and natural cycles. SAB odds did not differ between groups among OM and natural cycles but were lower in the FROZEN group among gonadotropin cycles [adjOR (95% CI): 0.13 (0.02–0.98), ref.: FRESH]. There were no differences in CP and SAB in the performed subanalyses (limited to first cycles or partner's sperm only, after excluding female factors, or after stratification according to female age). Nevertheless, time to conception was slightly longer in the FROZEN compared to the FRESH group (3.84 vs. 2.58 cycles, p < 0.001). No significant differences were present in LB and cumulative pregnancy results, other than in the subgroup of natural cycles, where higher LB odds [adjOR (95% CI): 1.08 (1.05–1.12)] and higher cumulative pregnancy rate (34% vs. 15%, p = 0.002) were noted in the FROZEN compared to the FRESH group. Conclusion Overall, clinical outcomes did not differ significantly between frozen and fresh sperm IUI cycles, although specific subgroups might benefit from fresh sperm utilization.